The Missing Teacher: Contradictions and Conflicts in the Experience of Online Learners - Dippe, Günther (Proceedings of the International Conference on Networked Learning, 2006)
A nationwide Swedish distance education programme, SÄL, was offered to adults with previous higher education studies working as teachers in K-12. A smaller study conducted among this group of students at Göteborg University, Göteborg, revealed concerns regarding teacher performance online. A follow-up and larger study using a questionnaire survey was used to reveal possible conflicts and contradictions in the programme. An analysis suggests that there is a contradiction between how the programme is presented and how it is carried out in a number of cases. There are also conflicts, not only between teachers and students, but also between senior university management and some of the course leaders/teachers. The study found that the students perceived many teachers as being absent in the discussions online. Teacher importance for student knowledge-building also scores very low compared, for example, with face-to-face meetings.